FLT PET/CT Is Better Than FDG PET/CT in Differentiating Benign From Malignant Pancreatobiliary Lesions. (May 2016) - Vineeth Kumar, P.M.; Verma, G.R.; Mittal, B.R.; Agrawal, Kanhaiyalal; Gupta, Rahul; Kochhar, Rakesh; Singh, Virendra; Kaman, Lileshwar; Singh, Rajinder
Abstract : Purpose: 18 F-fluorothymidine (FLT), unlike FDG, is incorporated exclusively into DNA and is considered a specific marker of cell proliferation. The role of FLT PET/CT scan in differentiating benign from malignant pancreatobiliary tumors is unknown. Patients and Methods: Twenty-five suspected pancreatobiliary tumors on contrast-enhanced CT (CECT) scan in 23 patients were evaluated by FDG PET/CT and FLT PET/CT scans. The histopathology or fine-needle aspiration cytology was considered as criterion standard for the diagnosis. Surgeons were blinded to FLT PET/CT results. Management decision was guided by clinical and CECT scan and FDG PET/CT. Results: Five of 23 patients had metastatic disease on CECT imaging. The remaining 18 underwent exploratory laparotomy. Two of them had synchronous lesions. Histopathology/fine-needle aspiration cytology confirmed malignancy in 17 lesions and benign disease in the remaining 8 lesions. All 8 benign lesions were negative on FLT PET/CT. Seven of the 8 benign lesions were clinically diagnosed as malignancy on CECT and FDG PET/CT. The specificity, positive predictive value, and accuracy were higher for FLT PET/CT (100%, 100%, and 92%) compared with CECT (12.5%, 70.83%, and 72%) and FDG PET/CT (12.50%, 69.57%, and 68%). However, the sensitivity of FLT PET/CT (88.24%) was similar to CECT (100%) and FDG PET/CT (94.12%). Conclusions: Molecular-based FLT PET/CT is a better imaging than FDG PET/CT in differentiating benign from malignant lesions in the pancreatobiliary region. It has a potential to bring down the incidence of preventable radical resection in suspected pancreatobiliary tumors.